Legal Protection of Migrant Workers' Rights Seen from the Perspective of International Law - Wandi Subroto (LEGAL BRIEF, 2022)
Indonesia is one of the most significant contributors to migrant workers globally. It is proven that migrant workers have contributed a large amount of foreign exchange and helped the Indonesian economy. However, the positive contribution made by migrant workers is not accompanied by appropriate legal protection provided by the government, even though various regulations have been made. We still hear a lot of problems related to migrant workers ranging from victims of human trafficking, victims of violence by employers, and various other acts of violence. It is for these reasons that this research will examine the legal protection of migrant workers' rights from the standpoint of international law, with a focus on the Universal Declaration of Human Rights (UDHR), International Covenant on Economic, Social and Cultural Rights (ICESCR), International Convention on the Protection of the Rights Of Migrant Workers And Members Of Their Families, and The ASEAN Declaration on the Protection Of The Rights Of Migrant Workers A normative juridical approach (statue and conceptual) is used in this article's study methodology (conceptual approach). Library books and scientific works, as well as articles and papers relating to research material are used as secondary data in this composition.